Minutes of 2nd technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 2nd Technical and Progress Monitoring (TPM) (session II) meeting of BRACU new campus, held on 27th October, 2018.